Alopecia (Homoeopathy for All, 2024)
Alopecia is a condition  characterized by hair loss from the  scalp or other areas of the body. It  is a multifactorial disorder with  significant psychological impacts,  affecting an individual’s well being and quality of life. Insights  from dermatology, genetics,  immunology, and endocrinology are  vital in understanding this complex  condition.
Keywords: dermatology; experience